Assessing student learning in selected social sciences and humanities undergraduate programmes at universities in the UK and Vietnam: a comparative case study - Nguyen, Thi Hong Tham (2013)
This research study investigates the similarities and differences in assessment policy, perspectives and practices in relation to student learning, desirable graduate outcomes and lifelong learning (LLL) in two departments with similar disciplines: Sociology and Social Policy and English Studies of the Midlands University (MU) – UK and Sociology and English Linguistics and Literature of the Ho Chi Minh City University (HCMU) – Vietnam. The study’s conceptual framework was developed from research literatures on assessment, mainly David Boud’s framework of sustainable assessment or assessment for longer term learning, as the framework for data analysis. The methodology is a comparative case study, and the methods include using semi-structured interviews with 22 staff in both cases, four student focus groups, an action-based intervention at the English department of the HCMU, and document analysis. The similarities and differences across the comparative cases are explained on the basis of the economic, socio-cultural and HE contexts, while Boud’s framework is reframed theoretically and operationally for these contexts, and as a guide to improving practices.